Tx-Rx lens-based satellite-on-the-move Ka-band antenna - Silva, J. S.; Lima, E. B.; Costa, J. R.; Fernandes, C. A.; Mosig, J. (IEEE Antennas and Wireless Propagation Letters, 2015)
A simple low-cost mobile ground terminal antenna for Ka-band satellite communications is presented. The antenna is composed of a shaped dielectric lens which tilts and rotates in front of a feed to direct the beam. The wideband feed system is composed of a quad-ridged horn with a 45º slant aperture and a coaxial-to-quad-ridged circular waveguide transition. The lens allows simple mechanical beam steering from 0º to 65º in relation to the zenith and 360º in azimuth by rotating both the lens and the feed slanted aperture. Performance measurements of a manufactured prototype prove the beam tilting capabilities in elevation with a maximum gain of 22 dBi and scan loss below 3 dB at 20 GHz and 24 dBi gain with less than 4.5 dB scan loss at 30 GHz.